Load frequency control for multi-area power system with two-source using sliding mode control - Thai Phan, Quoc; Lam-The Tran, Thinh; Tuan Le, Phat; Bao Ho, Dinh; Van Huynh, Van (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
A consistent electrical supply relies on the stability of power systems. In changing load conditions, control methods like load frequency control (LFC) are essential for safeguarding its stability. Conventional methods of LFC frequently encounter uncertainties in the system, external disruptions, and nonlinearities. This article introduces a more sophisticated method for managing load frequency and improving LFC in power systems through the utilization of sliding mode control (SMC). SMC provides strong stability and resilience against nonlinearities and disturbances, making it a promising method to overcome the drawbacks of traditional control techniques. We offer an in-depth examination of the second-order-integral SMC (SOISMC) method specifically designed for LFC, covering the creation and execution of the control algorithm. The method being suggested utilizes a sliding/gliding surface to maintain the system trajectories as continuous on the surface even with changes in parameters and external disturbances. Simulation results show big enhancements in frequency stability and system performance when compared to conventional proportional-integral-derivative (PID) controllers. The article also features a comparison between SOISMC and other contemporary control methods, emphasizing its strength in terms of resilience and flexibility.